The paradoxes experienced by informal caregivers of people with dementia during the transition from home to a nursing home. (2nd February 2022) - Groenvynck, Lindsay; de Boer, Bram; Beaulen, Audrey; de Vries, Erica; Hamers, Jan P H; van Achterberg, Theo; van Rossum, Erik; Khemai, Chandni; Meijers, Judith M M; Verbeek, Hilde
Abstract: Background: The transition from home to a nursing home is a common care process experienced by older persons with dementia and their informal caregivers. This transition process is often experienced as fragmented and is paired with negative outcomes for both older persons (e.g. mortality) and informal caregivers (e.g. grief). Due to the central role that informal caregivers play, it is crucial to capture their experiences throughout all phases of the transition. Methods: A secondary data analysis was conducted using an interpretative phenomenological design. A total of 24 informal caregivers of older persons with dementia, moving to a nursing home, participated in in-depth interviews. Data were collected between February 2018 and July 2018 in the Netherlands. Data were analysed using Interpretative Phenomenological Analysis. Results: The transition experiences are characterised by three paradoxes: (i) contradicting emotions during the transition process; (ii) the need for a timely transition versus the need to postpone the transition process and (iii) the need for involvement versus the need for distance. All paradoxes are influenced by the healthcare system. Conclusions: The identified paradoxes show the impact of the healthcare system and the importance of timely planning/preparing for this transition on the experiences of informal caregivers. In addition, it provides healthcare professionals insight into the thought processes of informal caregivers. Future research can use these paradoxes as a foundation to develop innovations aiming to improve the transition process from home to a nursing home for informal caregivers and, consequently, older persons.